Pengaruh Audit Tenure, Audit Capacity Stress, dan Entrenchment Effect Terhadap Kualitas Audit: Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia (BEI) 2019-2022 - Deni Rahmadani; Halmawati Halmawati (Universitas Negeri Padang, 2024)
This research examines the association of audit tenure, audit capacity stress, and entrenchment effect as independent variables on audit quality. This research was conducted at manufacturing companies listed on the Indonesia Stock exchange from 2019-2022. This research is important to do considering the literature review shows inconsistent results on each research variable. The research sample was selected through purposive sampling method and using multiple regression as the basis of analysis. The results of the research and hypothesis testing that have been carried out show that the first hypothesis is accepted where there is a significant negative effect between audit tenure and the quality of the audit results. The second hypothesis is rejected where there is no significant effect between audit capacity stress on the quality of audit results. The third hypothesis is rejected, where there is no effect of the entrenchment effect on the quality of audit results.